2011
DOI: 10.1111/j.1365-2214.2011.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between motor competence, physical fitness and self‐perception in children

Abstract: The results indicated a strong relationship between physical fitness, motor competence and self-perception in children that varied by gender. This implies that all these factors are essential contributions in order to facilitate participation in physical activity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
6
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 47 publications
10
77
6
10
Order By: Relevance
“…Consistent with the literature, the children with p DCD in the present study also showed lower physical fitness in the components of muscle strength and endurance and explosive power [5][6][7]24,25 . Physical fitness tests commonly used for assessment of these components are the Curl-up, Push-up, Standing broad jump and Medicine ball chest pass tests.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with the literature, the children with p DCD in the present study also showed lower physical fitness in the components of muscle strength and endurance and explosive power [5][6][7]24,25 . Physical fitness tests commonly used for assessment of these components are the Curl-up, Push-up, Standing broad jump and Medicine ball chest pass tests.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, the results of the present study are similar to a number of previous studies that did not match the groups in terms of normal BMI for age 5,7,24 . A number of studies, especially those using field-based protocols, such as the Legér 20-m shuttle run 5,7,13,19,24 , the 6-m run 6,24,25 and the 800-m run 5 , have consistently found that cardiorespiratory fitness in children with p DCD is lower than that in TD children. Among the variables accounting for the poor cardiorespiratory fitness of these children are the perceptions of the subjects' own abilities in which children with p DCD do not feel physically as adequate compared with TD children 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Las conclusiones de estos estudios ponen de relieve los vínculos existentes entre factores como la fuerza o la capacidad cardiorrespiratoria con medidas generales de autoconcepto y otras específicas como el autoconcepto físico, intelectual o social (Guillén y Ramírez, 2011;Petty, Davis, Tkacz, Young-Hyman y Waller, 2009;Sherrill, Holguin y Caywood, 1989;Strong et al, 2005;Vedul-Kjelsäs, Sigmundsson, Stensdotter y Haga, 2012;Velez et al, 2010). En la presente investigación, aunque la velocidad, la flexión profunda de tronco y el salto horizontal han correlacionado significativamente con las diferentes dimensiones del autoconcepto estudiado, el consumo máximo de oxígeno es la medida que más relevancia ha tenido.…”
Section: Discussionunclassified
“…De hecho, tienden a ser las personas con mejor autoconcepto físico aquellas que muestran mayor implicación y adherencia a las actividades deportivas (Annesi, Unruh, Marti, Gorjala y Tennant, 2011;Borrego et al, 2012;Fernández et al, 2010), por lo que el autoconcepto físico se torna esencial de cara a potenciar y aumentar la realización de dichas actividades (Scarpa, 2011;Vancampfort et al, 2011;Vedul-Kjelsås, Sigmundsson, Stensdotter y Haga, 2012), tan necesarias para evitar enfermedades crónicas, hábitos nocivos de inactividad o consumo de sustancias (Ceschini, Andrade, Oliveira, Araujo y Matsudo, 2009), así como para promocionar la salud mental (Haugen et al, 2013) y el bienestar (Guedes, Souza, Ferreirinha y Silva, 2012;Rahmani-Nia, Damitchi, Azizi y Hoseini, 2011).…”
Section: Introductionunclassified